Pd–Cu Bimetallic Tripods: A Mechanistic Understanding of the Synthesis and Their Enhanced Electrocatalytic Activity for Formic Acid Oxidation. (16th September 2014) - Zhang, Lei; Choi, Sang‐Il; Tao, Jing; Peng, Hsin‐Chieh; Xie, Shuifen; Zhu, Yimei; Xie, Zhaoxiong; Xia, Younan
<x xml:space="preserve">Abstract</x> This article reports a facile synthesis of Pd‐Cu bimetallic tripods with a purity over 90%. Two requirements must be met in order to form tripods: i) formation of triangular, plate‐like seeds during the nucleation step and ii) preferential deposition of atoms onto the three corners of a seed during the growth step. In this synthesis, these requirements are fulfilled by adding CuCl2 and KBr into an aqueous synthesis. Specifically, it is demonstrated that the Cu atoms resulting from underpotential deposition could greatly reduce the energy barrier involved in the formation of triangular seeds with planar defects because of the much lower stacking fault energy (41 mJ·m−2 for Cu vs 220 mJ·m−2 for Pd). The Br− ions could strongly bind to the three {100} side faces of a triangular seed, forcing the Pd atoms to grow from the three corners of a seed to generate a tripod. When compared with commercial Pd black, the Pd‐Cu tripods exhibited substantially enhanced catalytic activity toward the electro‐oxidation of formic acid. This work offers a general strategy for the synthesis of nanocrystals with a tripod structure for catalytic applications.